PENGARUH TEKNIK COPY THE MASTER (CTM) BERBANTUAN MEDIA BOARVEL TERHADAP KETERAMPILAN MENULIS TEGAK BERSAMBUNG SISWA KELAS IV SD - Putri Negari, Pratiwi; Malihatul Hawa, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ cursive handwriting skills in elementary schools, particularly in terms of neatness, letter formation, letter connectivity, and writing cleanliness. These conditions indicate the need for innovative learning strategies to improve students’ writing skills. One effort that can be implemented is the application of the Copy the Master technique assisted by BOARVEL media in the learning process. The aim of this study was to determine the effect of the Copy the Master technique assisted by BOARVEL media on students’ cursive handwriting skills in elementary school. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The population of this study was fourth-grade elementary school students. The sample consisted of an experimental class that received treatment using the Copy the Master technique assisted by BOARVEL media and a control class that used conventional learning. Data collection techniques included performance tests of cursive handwriting skills, observation, documentation, and questionnaires. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing with the t-test. The results showed that there was a difference in cursive handwriting skills between students who learned using the Copy the Master technique assisted by BOARVEL media and those who used conventional learning. The average post-test score of the experimental class was higher than that of the control class. Therefore, it can be concluded that the Copy the Master technique assisted by BOARVEL media has a positive effect on improving elementary school students’ cursive handwriting skills.